Versatile platform of nonlocal metasurfaces for both spectral and spatial control of light waves - Run Chen; Shuming Wang (Light: Science & Applications, 2022)
Abstract Multifunctional nonlocal metasurfaces based on quasi-bound states in the continuum are experimentally demonstrated, which shapes the wavefronts at the resonant wavelengths while have no effect on other wavelengths. By means of cascade and orthogonal perturbations, the nonlocal metasurface devices can be extended to a versatile platform with multifunction.